Organización con participación comunitaria y estatal con grupos de adultos mayores del departamento del Guaviare - Galvez Londoño, Benjamin (Universidad de San Buenaventura - Cali, 2017)
The decision to make this project degree, due to the experience gained from working as gerontological counselor at home friend for seniors, (HOGAMI) in San José del Guaviare, for a three-month contract, and looking many needs of the elderly in the areas of health, social welfare, ludicodeportivas activities and physical plant, we set forward various actions and started giving priority to health. In this area the internal HOGAMI. They were cared for by a guard who in turn supplied medicines and transferred them to the hospital in case of appointments, and errands to get care, medicines and other formulated elements. We set out to make arrangements with the secretary of health department and the benefit of nursing service 24 hours medical service in the HOGAMI was obtained. Wednesdays and delivery of medicines at the point, besides stretcher, stairs, desk, chairs, material and suture kit provided.